[Zemstvo statistics] : [Russia c. 1870-1917 : on microfiche] - Moiseenko, T. L. (Tatʹ︠i︡ana Leonidovna); Kerblay, Basile H.; Pries, Anne (IDC, 1966)
Statistical material published by the Zemstvo, as well as general works and local studies in this field. Material concerns agrarian development and the peasantry of the 19th-20th centuries and includes demographic statistics, data on health and medical care, primary education and libraries, meterological data, data about large estates, handcrafts and industry in cities.